2017
DOI: 10.1155/2017/4089019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Herbal Medicine Users and Adverse Events Experienced in South Korea: A Survey Study

Abstract: Background. This survey aimed to investigate the characteristics of users and nonusers of herbal medicine and the adverse events experienced due to herbal medicines in South Korea. Methods. The questionnaire consisted of safety, using experience, using type, usage and nonusage reason, purchase location, and adverse events of herbal medicine. The survey was administered by online. Results. Of the total 1,134 respondents, 726 (64.0%) considered herbal medicine safe, and 693 (61.1%) answered that they have taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…Thirty papers in condition-specific populations [ 45 , 47 , 65 , 75 , 79 , 80 , 95 , 107 , 115 , 120 , 123 , 124 , 130 , 150 , 152 , 157 , 162 , 168 – 179 ], six in general populations [ 180 185 ], one publication involving elderly people [ 53 ] and one publication involving females [ 61 ] reported the reasons for not using CAM. Asian populations more frequently reported doubt about the efficacy of CAM or lower effectiveness of CAM compared to CM, concerns about side effects of CAM, and inconvenience or unavailability of CAM than did members of Western populations ( p < 0.05), Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty papers in condition-specific populations [ 45 , 47 , 65 , 75 , 79 , 80 , 95 , 107 , 115 , 120 , 123 , 124 , 130 , 150 , 152 , 157 , 162 , 168 – 179 ], six in general populations [ 180 185 ], one publication involving elderly people [ 53 ] and one publication involving females [ 61 ] reported the reasons for not using CAM. Asian populations more frequently reported doubt about the efficacy of CAM or lower effectiveness of CAM compared to CM, concerns about side effects of CAM, and inconvenience or unavailability of CAM than did members of Western populations ( p < 0.05), Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] In addition, curcumin, from CLR, is known to have excellent antitumor effects and to reduce TRAIL resistance in prostate cancer. [ 12 ] However, clinically, herbal medicines are most commonly used as decocted aqueous extracts,[ 13 ] and to date, no study has investigated the effects of total-herb aqueous extracts of CR and CLR on overcoming TRAIL resistance in NSCLC. In this study, CR and CLR aqueous extracts have been shown to not only act synergistically with TRAIL but also to overcome TRAIL resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gender roles may be associated with engagement in certain health behaviors-given that wives usually take on the role of family caregivers. Herbal medicine is often taken as a supplement for health improvement among Koreans; about 57% of Korean adults who consumed herbal medicine reported that they used herbal medicine for "health improvement" (S. Jang et al, 2017). In addition to taking supplements, restricting food consumption is also a type of behavior in which adults engage to control their dietary intake (i.e., cholesterol, sodium; H. M. Choi et al, 2018).…”
Section: Health Behavior Concordance Within Couplesmentioning
confidence: 99%